Female participation in the construction industry: A review on the issues and barriers / Anis Sahira Baharuddin - Baharuddin, Anis Sahira (2021)
The lack of awareness has resulting in the existence of issues and barriers that are faced by females relating to their participation in the construction industry. Due to the image of the construction industry, female workers are more bound to be facing issues and barriers throughout their career rather than male workers. Thus, it is important to distinguish the factors that contributes t the problem and find a sway and suggestion in order to create awareness and improve the female worker’s welfare in the construction industry generally. This research’s goal is to achieve this key factors and distinguish them on their importance that are related and contributes to the issues and barriers faced by female workers, and it is also this research's goal to create awareness on this issue by suggesting and recommending the ways to improve the awareness for this problem. This research is based on the data obtained by online questionnaires that are participated by companies that are closely related to the construction industry. The data was analyzed in order to determine the importance level of each of the listed key factors based on their mean score and the ways to approach and tackle the recommendation of creating and improving the awareness of the issue and barriers faced by women regarding their participation in the construction industry.